The acquisition of Swedish grammar - Josefsson, Gunlög; Platzack, Christer, 1943-; Håkansson, Gisela (Language acquisition & language disorders, 2003)
This book provides a number of studies of different aspects of Swedish child language. Some of the thematic chapters present original, unpublished data: on the acquisition of tense, on the range and frequency of different word order patterns in early child Swedish, related to the input, meaning the language of adults talking to the children or in the presence of the children. The remaining chapters present overviews of previous research: on the acquisition of word formation rules, the noun phrase, and wh-questions. The introduction to this volume contains a concise overview of the basic features of Swedish grammar and a comprehensive overview of different Swedish child language corpora. The main body of research proceeds within a generative framework, but the text is designed to be accessible to researchers of different theoretical paradigms.